Behavior and Emotive Predictors of Cognitive Flexibility: The Influence of Bedtime Procrastination and Fear of Missing-out - Iram Naz (Corresponding author); Khadija Mujahid (Journal of Religion and Society, 2025)
The present study examined bedtime procrastination and fear of missing out as predictor of cognitive flexibility in young adults. Bedtime procrastination has become increasingly common due to poor self-regulation and excessive social media use, and FoMO is largely driven by social connectivity pressure and tis is linked with emotional distress and disrupted sleep pattern. Quantitative correlational research design was employed, data was collected from 200 people involving young adults aged 18-24, who completed the questionnaire. Scales used for this purpose are all standardized. Measure include Bedtime Procrastination scale, Fear of Missing Out scale, and Cognitive Flexibility scale. SPSS version 24, descriptive statistics, Pearson correlation, regression analysis were employed for data analysis. The findings showed that there was significant relationship between bedtime procrastination and cognitive flexibility, whereas fear of missing out had significant negative correlation with cognitive flexibility. Furthermore, regression analysis shows predictive relationship of bedtime procrastination and fear of missing out on cognitive flexibility, higher bedtime procrastination leads to increase in cognitive flexibility whereas higher fear of missing out decrease cognitive flexibility. Keywords: Bedtime Procrastination, Fear of Missing Out, Cognitive Flexibility